(How) should the language policy promote mother-tongue instruction or a straight-for-English approach in primary schooling in South Africa: what does empirical data contribute? - Mohohlwane, Nompumelelo Lungile (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.